PHYSIOLOGICAL RESPONSES OF SABURAI GOAT ON THE OF ADDITION DIETARY PROTEIN LEVEL - Adhianto, Kusuma; ., Muhtarudin; Sulastri, Sulastri; Hartono, Madi (Jurnal Kedokteran Hewan, 2017)
The purpose of this research was to study the effect of different level of protein addition in goat ration on feed addition in the ration on feed intake and physiological responses of Saburai goats (rectal temperature, respiratory rate, and heart rate). Twenty male Saburai goats were randomly divided into 4 treatments group with 5 goats each. Goats in group 1 (PO) were fed with forage, while goats in group 2 (P1), 3 (P2), and 4 (P3) were fed with forage + concentratre with 13%, 16%, and 19% crude protein, respectively. The treatments were P0= feeding forage, P1= feeding forage + concentrate with 13% crude protein (CP), P2= feeding forage + concentrate with 16% CP, and P3 feeding forage + concentrate with 19% CP. The results showed that the rectal temperature and heart rate did not significantly affected (P0.05) in all treatment, however the heart rate was significantly (P0.05) affected among the treatments. The conclusion is the addition of different protein level in the ration has no effect on rectal temperature and respiratory rate, but significantly increases the heart rate frequency.